Secondary battery

By using amorphous titanium oxide as the negative electrode material and protonic ionic liquid as the electrolyte in a proton secondary battery, the problem of irreversible hydrogen generation caused by aqueous electrolytes is solved, and the charging and discharging efficiency and cycle stability of the battery are improved.

JP2025069746APending Publication Date: 2025-05-01SHINSHU UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023179660
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-18
Publication Date
2025-05-01

AI Technical Summary

Technical Problem

In proton secondary batteries using aqueous electrolytes, electrolyteization of water leads to irreversible generation of hydrogen, resulting in the disappearance of protons as carriers, thereby reducing the charge and discharge efficiency and self-discharge behavior of the battery.

Method used

The combination of an electrolyte of a negative electrode material containing amorphous titanium oxide and a proton ionic liquid is used to control the transport of protons or hydroxide ions, prevent the electrolysis of electrolytic water, and thus inhibit the irreversible formation of hydrogen.

Benefits of technology

It effectively suppresses the irreversible generation of hydrogen, improves the charge and discharge efficiency, and improves the cycle stability and self-discharge performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025069746000001_ABST
    Figure 2025069746000001_ABST
Patent Text Reader

Abstract

To provide a secondary battery that can suppress irreversible hydrogen generation and improve coulomb efficiency in the secondary battery in which reversible charging and discharging is performed by the movement of a proton or a polyatomic ion composed of hydrogen atoms and non-metal atoms such as hydronium ion (H3O+) between the positive and negative electrodes.SOLUTION: A secondary battery 1 according to the present invention is a secondary battery in which reversible charging and discharging is performed by the movement of protons, or polyatomic ions composed of hydrogen atoms and non-metal atoms, between the positive electrode 2 and the negative electrode 4, and a negative electrode active material 4B contains an amorphous titanium oxide, and an electrolyte 5 (electrolyte composition) contains an ionic liquid.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a secondary battery. [Background technology]

[0002] In secondary batteries that can be reversibly charged and discharged, the mainstream is those that use metal cations as charge carriers, such as lithium ions (Li + Lithium-ion secondary batteries (LIBs) that use Na (Na) as a carrier ion are widely used in a wide range of fields. However, in recent years, the diversity of carrier ions has been emphasized for LIBs due to the instability of supply caused by uneven distribution of lithium (Li) resources, which is the ion source of LIBs. + ), K(K + ), Ca(Ca 2+ ), Mg(Mg 2+ Efforts are being made to research and develop secondary batteries that utilize s-block elements such as ZnO.

[0003] In contrast, the present inventors have developed a method for producing protons (H + ) between the positive and negative electrodes, protons or hydronium ions (HO + We are currently conducting research into a secondary battery (hereinafter sometimes referred to as a "proton secondary battery") in which reversible charging and discharging is achieved by the movement of polyatomic ions consisting of hydrogen atoms and nonmetallic atoms such as hydrogen and hydrogen atoms (H3O). Protons are the lightest of all ions and have a small ionic radius, which makes them advantageous for ion transport. Protons are also loaded onto the battery as polyatomic ions consisting of hydrogen atoms and nonmetallic atoms, and are transported as hydronium ions (HO). + ), ammonium ion (NH4 + ) can move through the electrolyte by diffusion. Protons can also move through chains of water molecules connected by hydrogen bonds, such as H + or OH - Rapid proton conduction is possible through the Grothas mechanism, a mechanism in which the transfer of protons and the rearrangement of hydrogen bonds proceed cooperatively. [Prior art documents] [Non-patent literature]

[0004] [Non-Patent Document 1] Masahiro Shimizu, Daisuke Nishida, Ayaka Kikuchi, and Susumu Arai, American Chemical Society (US), The Journal of Physical Chemistry C, 2023;127(36):17677-17684 Summary of the Invention [Problem to be solved by the invention]

[0005] In proton secondary batteries, when they are operated in an aqueous electrolyte with polyatomic ion conductivity consisting of protons or hydrogen atoms and nonmetallic atoms, there is a problem that irreversible hydrogen (H2) generation occurs due to a side reaction such as electrolysis of water. This causes the protons to disappear as charge carriers. In addition, if the pH of the negative electrode interface increases due to the disappearance of protons, self-discharge behavior in which protons absorbed in the negative electrode active material undergo a neutralization reaction and are released, or reductive decomposition of cationic components in the electrolyte may occur. As a result, the ratio of discharge capacity to charge capacity decreases, and the Coulombic efficiency (charge / discharge efficiency), which indicates the reversibility of charge / discharge, decreases.

[0006] In response to this, the present inventors have made improvements, such as using rutile titanium oxide (R-TiO2), which has a conduction level on the more positive side than brookite and anatase types of titanium oxide (TiO2), as the negative electrode active material, as described in Non-Patent Document 1, and applying a buffer solution to the electrolyte composition to make it difficult for the pH of the electrolyte to change. However, there is still room for further improvement. [Means for solving the problem]

[0007] The present invention has been made in view of the above circumstances, and provides a method for transferring protons or hydronium ions (HO + The present invention aims to provide a secondary battery in which reversible charging and discharging is performed by the movement of polyatomic ions consisting of hydrogen atoms and non-metallic atoms, such as hydrogen atoms and non-metallic atoms, and the like, and which can suppress irreversible hydrogen generation and improve Coulombic efficiency.

[0008] The present invention solves the above problems by the solution means described below as one embodiment.

[0009] The secondary battery of the present invention is a secondary battery in which reversible charging and discharging is performed by the movement of protons or polyatomic ions composed of hydrogen atoms and non-metallic atoms between a positive electrode and a negative electrode, and is characterized in that the negative electrode active material contains amorphous titanium oxide and the electrolyte composition contains an ionic liquid.

[0010] The titanium oxide is TiO x Amorphous TiO consisting of titanium and oxygen atoms with the composition (x is a positive number). x The compound can be applied.

[0011] The TiO x The compound may be a hydrolysate of a crystalline titanium oxide salt. For example, the titanium oxide salt may be tetraisopropyl orthotitanate, and the TiO x The compound that can be applied is a hydrolysis product of tetraisopropyl orthotitanate with ethyl alcohol.

[0012] As the ionic liquid, a protic ionic liquid can be suitably used. Effect of the Invention

[0013] According to the present invention, in a proton secondary battery, irreversible hydrogen generation can be suppressed and the coulombic efficiency can be improved. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a schematic cross-sectional view showing a part of a secondary battery according to an embodiment of the present invention. [Diagram 2] Fig. 2A shows X-ray diffraction patterns using CuKα radiation for the powders of Examples 1, 2, and 3. Fig. 2B shows X-ray diffraction patterns using CuKα radiation for rutile-type titanium oxide (IV) (R-TiO2) powder. [Diagram 3] Fig. 3A is a graph showing the results of a constant current charge / discharge test according to Example 4. Fig. 3B is a graph showing cycle characteristics (changes in discharge capacity and coulombic efficiency) based on the constant current charge / discharge test according to Example 4. [Figure 4] FIG. 4 is a graph showing the results of a constant current charge / discharge test according to Reference Example 1. [Diagram 5] FIG. 5 is a graph showing the results of a constant current charge / discharge test according to Reference Example 2. [Figure 6] FIG. 6 is a graph showing the results of a constant current charge / discharge test according to Comparative Example 1. In FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] [Secondary battery] Hereinafter, an embodiment of the secondary battery of the present invention will be described with reference to the drawings. FIG. 1 is a schematic cross-sectional view showing a part of a secondary battery 1 according to an embodiment of the present invention. As shown in FIG. 1, the secondary battery 1 includes a positive electrode 2, a negative electrode 4, a separator 3, and an electrolyte 5. Note that the term "electrolyte composition" used in this specification is synonymous with the electrolyte 5, but when focusing on the components of the electrolyte 5, it may be referred to as the "electrolyte composition". When the electrolyte 5 is a liquid, it may be referred to as the "electrolyte solution".

[0016] The positive electrode 2 is formed by laminating a positive electrode active material 2B on the surface of a positive electrode substrate 2A as a positive electrode current collector. The negative electrode 4 is formed by laminating a negative electrode active material 4B on the surface of a negative electrode substrate 4A as a negative electrode current collector. The separator 3 and the electrolyte 5 are disposed so as to be interposed between the positive electrode 2 and the negative electrode 4. Furthermore, the secondary battery 1 includes a positive electrode exterior material 6 and a negative electrode exterior material 7. The positive electrode exterior material 6 and the negative electrode exterior material 7 respectively exteriorize the positive electrode side and the negative electrode side, respectively, and the positive electrode exterior material 6 and the negative electrode exterior material 7 respectively function as a positive electrode terminal and a negative electrode terminal. The positive electrode 2, the negative electrode 4, the separator 3, and the electrolyte 5 are appropriately fixed with a ring member (not shown) or the like so as to be disposed in the above-mentioned predetermined positional relationship as shown in FIG. 1, and are exteriorized with the positive electrode exterior material 6 and the negative electrode exterior material 7 so as to encapsulate them, thereby manufacturing the secondary battery 1 according to this embodiment.

[0017] As the secondary battery 1 of this embodiment, a coin type or button type is exemplified as shown in FIG. 1, but the secondary battery of the present invention may be in any form that a secondary battery can take, and may also be configured in a sheet type, a laminated type, a cylindrical type, or the like.

[0018] In the secondary battery 1 of this embodiment, protons (H + ), or polyatomic ions consisting of hydrogen atoms and nonmetallic atoms, move to reversibly charge and discharge the proton secondary battery. An example of a polyatomic ion consisting of hydrogen atoms and nonmetallic atoms is the hydronium ion (HO + ), ammonium ion (NH4 + ) etc. That is, depending on the active materials 2B and 4B, protons are loaded as polyatomic ions, and H3O + , NH4 + etc. The concept of the secondary battery (proton secondary battery) of the present invention includes those in which protons substantially move between the positive electrode 2 and the negative electrode 4 in the form of these polyatomic ions. Note that polyatomic ions consisting of protons or hydrogen atoms and nonmetallic atoms may be referred to as "protons, etc."

[0019] (positive electrode) The positive electrode of the present invention may be in any form that a secondary battery can take. The positive electrode 2 according to this embodiment is configured in a form in which a coating film, which is a positive electrode active material layer having a positive electrode active material 2B, is formed on the surface of a metal foil, which is a positive electrode substrate 2A, as shown in FIG. 1. The positive electrode active material layer may be provided on at least a part of the surface of the positive electrode substrate 2A so as to be connectable to the negative electrode active material layer having a negative electrode active material 4B through at least an electrolyte 5 in terms of the function of the battery. Therefore, as an example, when the shape of the positive electrode substrate 2A is a sheet shape such as a metal foil, the coating film, which is a positive electrode active material layer, may be formed only on one side facing the negative electrode 4 in the sheet shape, as shown in FIG. 1, or may be formed on both sides (the entire surface of the sheet shape).

[0020] As an example of a method for producing the positive electrode 2, first, the positive electrode active material 2B is dispersed in a solvent together with a binder and a conductive assistant, etc., to synthesize a slurry. For the synthesis of the slurry, a known stirring device or grinding device such as a planetary mixer or a ball mill can be used. Next, the slurry is applied to a required portion of the surface of the positive electrode substrate 2A, and dried to volatilize the solvent, thereby forming a coating film (positive electrode active material layer) containing the positive electrode active material 2B on the surface of the positive electrode substrate 2A, thereby producing the positive electrode 2. Furthermore, as an optional operation, the formed coating film may be pressed for the purpose of increasing the density of the positive electrode active material 2B, etc. For the pressing, a known pressing device such as a roll press device can be used. In the above manufacturing example, the solvent may remain in the positive electrode active material layer to some extent. Alternatively, since the positive electrode active material layer can function as a battery as long as it has at least the positive electrode active material 2B, the solvent and / or the conductive assistant may not be blended. In addition, a thickener may be blended into the slurry as necessary.

[0021] The positive electrode substrate 2A basically functions as a support base for supporting a positive electrode active material layer formed by bonding the positive electrode active material 2B obtained as a powder, and further functions as a positive electrode current collector. In addition to conductive materials that are usually used for current collectors of secondary batteries, any material having conductivity can basically be used for the positive electrode substrate 2A. Examples include aluminum, aluminum alloys containing atoms other than aluminum, such as Mg, Zn, and Si, and stainless steel. In addition to metal foils made of these conductive materials, the form of the positive electrode substrate 2A according to this embodiment can also be made of a metal porous body such as a mesh or punched metal made of the same material.

[0022] As the positive electrode active material 2B, a material capable of inserting and detaching a polyatomic ion (proton, etc.) consisting of a proton or a hydrogen atom and a nonmetallic atom can be used. Such materials include carbon materials, transition metal oxides, organometallic complexes, conductive polymers, etc. Specific examples include activated carbon, molybdenum (VI) oxide (MoO3), vanadium (IV) oxide (VO2), tungsten (VI) oxide (WO3), molybdenum (IV) oxide (MoO2), Prussian blue analogs (e.g., ZnFe-PBA), 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA), and titanium oxides such as brookite, anatase, or rutile titanium oxides (B-TiO2, A-TiO2, R-TiO2), titanium niobium oxides represented by the chemical formula TiNb2O7, and hydrogen titanium oxides represented by the chemical formula H2Ti3O7. Of these, it can be said that a material having a relatively high potential for reacting with protons, etc. is more suitable as a positive electrode active material, and a material having a relatively low potential for reacting with protons, etc. is more suitable as a negative electrode active material, but functionally, either of them can be a positive electrode active material or a negative electrode active material. In this embodiment, since the negative electrode active material 4B is made of amorphous titanium oxide, a material having a higher potential for reacting with protons, etc. than the amorphous titanium oxide can be selected from the above materials and used as the positive electrode active material 2B.

[0023] In addition, the binder, thickener, conductive assistant, and solvent may be those that are usually used to form an active material layer of a secondary battery. A plurality of types of each may be used. For example, PVDF or the like may be used as the binder. For example, SBR, CMC, or the like may be used as the thickener. However, the distinction between the binder and the thickener is not clear, and there are cases where, for example, SBR or CMC is used as the binder. For example, acetylene black, Ketjen Black (registered trademark), Denka Black (registered trademark), or other carbon black may be used as the conductive assistant. For example, NMP, DMF, DMA, or the like may be used as the solvent.

[0024] (Negative electrode) The negative electrode of the present invention may have any form that a secondary battery can take, except that the negative electrode active material 4B is made of amorphous titanium oxide. As shown in FIG. 1, the negative electrode 4 according to this embodiment is configured in a form in which a coating film, which is a negative electrode active material layer having the negative electrode active material 4B, is formed on the surface of a metal foil, which is a negative electrode substrate 4A, in the same manner as the positive electrode 2. The negative electrode active material layer may be provided on at least a part of the surface of the negative electrode substrate 4A so as to be connectable to the positive electrode active material layer having the positive electrode active material 2B through at least the electrolyte 5 in terms of the function of the battery. Therefore, as an example, when the shape of the negative electrode substrate 4A is a sheet shape such as a metal foil, the coating film, which is a negative electrode active material layer, may be formed only on one side facing the positive electrode 2 in the sheet shape, as shown in FIG. 1, or may be formed on both sides (the entire surface of the sheet shape).

[0025] As in the case of the positive electrode 2, the negative electrode 4 may be produced by dispersing the negative electrode active material 4B in a solvent together with a binder and a conductive assistant to synthesize a slurry. For example, a known stirring device or grinding device such as a planetary mixer or a ball mill may be used to synthesize the slurry. The slurry is then applied to a required portion of the surface of the negative electrode substrate 4A, and dried to volatilize the solvent, thereby forming a coating film (negative electrode active material layer) containing the negative electrode active material 4B on the surface of the negative electrode substrate 4A to produce the negative electrode 4. As an optional operation, the coating film formed may be pressed for the purpose of increasing the density of the negative electrode active material 4B. For pressing, a known pressing device such as a roll press may be used. In the above production examples, the solvent may remain in the negative electrode active material layer to some extent. Alternatively, since the negative electrode active material layer can function as a battery as long as it has at least the negative electrode active material 4B, the solvent and / or the conductive assistant may not be blended. In addition, a thickener may be blended into the slurry as necessary.

[0026] The negative electrode substrate 4A basically functions as a support base for supporting a negative electrode active material layer formed by bonding the negative electrode active material 4B obtained as a powder, and further functions as a negative electrode current collector. In addition to conductive materials that are usually used for current collectors of secondary batteries, any material having conductivity can basically be used for the negative electrode substrate 4A. Examples include aluminum, aluminum alloys containing atoms other than aluminum, such as Mg, Zn, and Si, and stainless steel. In addition to metal foils made of these conductive materials, the form of the negative electrode substrate 4A according to this embodiment can also be made of a metal porous body such as a mesh or punched metal made of the same material.

[0027] The negative electrode active material 4B of this embodiment is made of amorphous titanium oxide. Regarding amorphous, when no peak is detected in the diffraction angle range related to crystalline titanium oxide in the X-ray diffraction pattern of the powder using CuKα rays, or when the peak is so weak that a person skilled in the art would normally judge that the titanium oxide is amorphous or highly likely to be amorphous, the titanium oxide can be said to be amorphous. In fact, as shown in the [Examples] described later, the examples using powders judged to be amorphous by X-ray diffraction achieve the object of the present invention, so that the present invention can define "amorphous" based on the criteria of the X-ray diffraction.

[0028] In addition, "titanium oxide" refers to an oxide containing titanium, and examples of "amorphous titanium oxide" include TiO x Amorphous titanium oxide such as TiO2, which is composed of titanium atoms and oxygen atoms and has the composition (x is a positive number), and Ti x Nb y O z (x, y, and z are positive numbers and may be the same or different), and includes amorphous materials consisting of titanium atoms, oxygen atoms, and other atoms. Ti x Nb y O z is an amorphous titanium niobium oxide such as TiNb2O7, and TiO x It is considered that Nb is partially doped in Nb-TiO x It can also be written as (where x represents a positive number).

[0029] Even if the constituent elements are the same, the chemical potentials of crystalline and amorphous materials are different. Therefore, we focused on titanium oxide, which is a material capable of inserting and extracting protons or polyatomic ions (protons, etc.) consisting of hydrogen atoms and nonmetallic atoms and can be used as an active material for proton secondary batteries. Titanium oxide has a relatively low potential for reacting with protons, etc., and is considered to be particularly suitable as a negative electrode active material. For example, it has been reported that the reaction potential range of rutile-type titanium (IV) oxide (R-TiO2) with protons, etc. is -0.9 to -0.42 V vs. SHE, and that of titanium niobium oxide represented by the chemical formula TiNb2O7 is -1.7 to -1.25 V vs. SHE. In contrast, the activation energy of the multi-step elementary process reaction related to the insertion of protons, etc. is smaller in the amorphous titanium oxides than in the crystalline ones, and it is considered that the reaction occurs at a higher potential (more positive potential). As shown in the Examples below, when amorphous titanium oxide is used as the negative electrode active material 4B, the reaction potential with protons and the like is shifted to a higher potential (more positive potential), thereby suppressing irreversible hydrogen generation that occurs at a lower potential, and a relatively good discharge capacity is obtained (Reference Example 1). Furthermore, when an ionic liquid is used in the electrolyte composition, irreversible hydrogen generation can be further suppressed, greatly improving the Coulombic efficiency, and thus stable and excellent cycle characteristics can be exhibited (Example 4).

[0030] In addition, even if crystalline and amorphous titanium oxides coexist in the active material (negative electrode active material) in one electrode (negative electrode), it is considered that no problems will usually occur based on the ordinary knowledge of a person skilled in the art. Therefore, from the [Examples] described later, it is found that even in the case where the negative electrode active material 4B is composed of amorphous titanium oxide as in this embodiment, and even in the case where crystalline and amorphous materials coexist, irreversible hydrogen generation can be suppressed compared to, for example, a proton secondary battery composed only of a conventionally known crystalline titanium oxide. For this reason, the negative electrode active material of the present invention can be generalized as a "negative electrode active material containing amorphous titanium oxide".

[0031] The synthesis of amorphous titanium oxide is carried out as follows: TiO x In the case of titanium oxide, for example, it can be synthesized by mixing a precursor crystalline titanium oxide salt with a solvent and hydrolyzing the mixture. The precursor titanium oxide salt is, for example, tetraethoxytitanium(IV) (TET) (CH 20 O4Ti), tetraisopropyl orthotitanate (TTIP) (C 12 H 28 Examples of the solvent include ethyl alcohol (EtOH) (C2H6O) and tetrahydrofuran (THF) (C4H8O). Specifically, as an example, first, 10 mL of TET and 50 mL of EtOH are mixed. Next, 3 mL of deionized water is dropped into the aqueous solution while stirring, and the solution is stirred for 30 minutes to hydrolyze the TET and produce amorphous TiO x The precipitate is then collected by centrifugation and dried at 80 °C in air to obtain powdered TiO x As another example, 7 g of TTIP and 150 g of THF are mixed. Then, 8 mL of deionized water is added dropwise to the aqueous solution while stirring, and the mixture is stirred for 30 minutes to hydrolyze TTIP and produce amorphous TiO. x The precipitate is then collected by centrifugation and dried at 80 °C in air to obtain powdered TiO x As another example, 10 mL of TTIP is mixed with 50 mL of EtOH. Then, 3 mL of deionized water is added dropwise to the aqueous solution while stirring, and the mixture is stirred for 30 minutes to hydrolyze TTIP and produce amorphous TiO. x The precipitate is then collected by centrifugation and dried at 80 °C in air to obtain powdered TiO x is obtained.

[0032] Also, Ti x Nb y O zIn this case, for example, it can be synthesized by the method described in JP 2015-084321 A. According to JP 2015-084321 A, first, a dilute sulfuric acid solution of titanyl sulfate (TiOSO4) and an ethanol solution of niobium chloride (NbCl5) are mixed so that the molar ratio of Nb / Ti is 7:3. Next, while stirring this mixed solution, the pH is adjusted to 8 with ammonia water. Next, the obtained solution is heated in an autoclave at 170°C for 5 hours, and then the solution is filtered and washed with pure water to obtain particles. It is described that when the structure of the particles thus obtained is analyzed by X-ray diffraction, a halo peak is observed and the particles are amorphous.

[0033] In addition, amorphous substances do not have a specific crystal structure, and even if the constituent elements are the same, the composition ratios of different combinations of precursors and solvents are not uniform, and it is impossible or almost impractical to directly identify them by their structure or characteristics. Therefore, in this specification, etc., such amorphous compounds (substances) may be specified as hydrolysates consisting of combinations of precursors and solvents (e.g., TET+EtOH, TTIP+THF, TTIP+EtOH, etc.).

[0034] In addition, the binder, thickener, conductive assistant, and solvent may be those that are usually used to form an active material layer of a secondary battery. A plurality of types of each may be used. For example, PVDF or the like may be used as the binder. For example, SBR, CMC, or the like may be used as the thickener. However, the distinction between the binder and the thickener is not clear, and there are cases where, for example, SBR or CMC is used as the binder. For example, acetylene black, Ketjen Black (registered trademark), Denka Black (registered trademark), or other carbon black may be used as the conductive assistant. For example, NMP, DMF, DMA, or the like may be used as the solvent.

[0035] (Separator) The separator 3 has a function of insulating the positive electrode 2 from contacting the negative electrode 4 without impeding the movement of polyatomic ions consisting of protons or hydrogen atoms and nonmetallic atoms. For the separator 3, a material having electrical insulation and ion conductivity that is usually used for separators in secondary batteries can be used. Examples include porous films made of polyolefins such as polyethylene (PE) and polypropylene (PP), aromatic polyamides, fluororesins, etc.

[0036] (electrolyte) The electrolyte 5 has polyatomic ion conductivity consisting of protons or hydrogen atoms and nonmetallic atoms, which allows the movement of polyatomic ions consisting of protons or hydrogen atoms and nonmetallic atoms. The electrolyte composition of this embodiment includes an ionic liquid. The ionic liquid is an ionically conductive liquid consisting of cations and anions of the salt itself. The ionic liquid referred to in this specification is a salt that has a low melting point (for example, 100°C or less) and exists in liquid form in the usage environment of the secondary battery 1, unlike high-temperature molten salts such as NaCl. For example, in the case of a secondary battery 1 intended to be used at room temperature (for example, 1-30°C), the ionic liquid refers to a room-temperature ionic liquid that exists in liquid form at least at that room temperature.

[0037] Unlike molecular solvents such as water, ionic liquids are ionically conductive liquids consisting of cations and anions of salt itself. Therefore, by applying ionic liquids to the electrolyte composition, a non-aqueous electrolyte that does not contain water can be applied to the secondary battery 1 (proton secondary battery) according to this embodiment, and electrolysis of water can be fundamentally prevented. As a result, irreversible hydrogen generation can be suppressed, and a relatively good discharge capacity can be obtained (Reference Example 2). Furthermore, by applying amorphous titanium oxide to the negative electrode active material 4B (test electrode active material), irreversible hydrogen generation can be further suppressed, and the Coulomb efficiency can be greatly improved, and stable and excellent cycle characteristics can be exhibited (Example 4).

[0038] Ionic liquids are classified into protic ionic liquids and aprotic ionic liquids. Protic ionic liquids are prepared by mixing a Bronsted acid and a Bronsted base, and are composed of a salt containing an onium ion generated by protonation. Regardless of whether they are protonic or aprotic, both can prevent electrolytic decomposition of water as a non-aqueous electrolyte, so at least one of protonic ionic liquids and aprotic ionic liquids may be applied as the electrolyte of the present invention. The electrolyte of this embodiment is selected and applied from either protonic or aprotic ionic liquid. When an aprotic ionic liquid is applied to the electrolyte composition of this embodiment, the ionic liquid is used as an electrolyte solvent, and an acid salt is mixed therewith to prepare the electrolyte 5 (electrolytic solution). That is, the electrolyte composition contains an ionic liquid as an electrolyte solvent. On the other hand, when a protonic ionic liquid is applied to the electrolyte composition of this embodiment, it can be used as the electrolyte 5 (electrolytic solution) as it is. That is, the electrolyte composition is made of an ionic liquid.

[0039] The cations that make up the ionic liquid are pyridinium-type cations that contain quaternary nitrogen (Cpy + , C4py + ), imidazolium type (C2mim + (EMI + ), C4mim + (BMI + ), C6mim + , C8mim + ), ammonium type (N 3,1,1,1 + , N 4,1,1,1 + , N 6,1,1,1 + , N 2,2,1,(2O1) + , Ch + ), pyrrolidinium type (Pyr 1,3 + , Pyr 1,4 + ), piperidinium type (Pip 1,3 + , Pip 1,4 + ) and phosphonium type containing quaternary phosphorus (P 5,2,2,2 +, P 6,6,6,14 + ) and other organic ions. The anions that make up the ionic liquid include TfO - , Tf2N - (TFSA - ), PF6 - , BF6 - The ionic liquid is a combination of these cations and anions. HTFSA and the like can be suitably used as an acid salt to be mixed with the aprotic ionic liquid as an electrolyte solvent. The melting point of the ionic liquid can be adjusted by adjusting the combination of the cations and anions, or the length of the alkyl group of the cation, for example. By this method, an ionic liquid according to the assumed usage environment of the secondary battery 1 may be prepared. Furthermore, acetic acid (AcOH), HTFSA, and the like can be suitably used as a Bronsted acid for preparing the protic ionic liquid. Im, DBU, and the like can be suitably used as a Bronsted base for preparing the protic ionic liquid. In the [Example] described later, a relatively good discharge capacity was obtained by applying an ionic liquid in which an imidazolium type and a pyrrolidinium type were selected as the cation (Reference Example 2).

[0040] (Exterior materials) The positive electrode exterior material 6 and the negative electrode exterior material 7 may be made of conductive materials that are typically used for exterior materials of secondary batteries, or may be made of any material that is conductive. One example is stainless steel. EXAMPLES

[0041] 1. Synthesis of amorphous titanium oxide An example of amorphous titanium oxide is amorphous TiO. x The compounds were synthesized using the following reagents: Tetraethoxytitanium(IV) (TET) (FUJIFILM Wako Pure Chemical Industries, Ltd.) Ethyl alcohol (EtOH) (Kanto Chemical) Tetraisopropyl orthotitanate (TTIP) (FUJIFILM Wako Pure Chemical Industries, Ltd.) Tetrahydrofuran (THF) (FUJIFILM Wako Pure Chemical Industries, Ltd.)

[0042] First, 10 mL of TET and 50 mL of EtOH were mixed. Then, 3 mL of deionized water was dropped into this aqueous solution while stirring, and the solution was stirred for 30 minutes. Then, the precipitate was centrifuged and collected, and heated at 80°C under an air atmosphere to obtain a powder (Example 1). Also, as another synthesis method, first, 7 g of TTIP and 150 g of THF were mixed. Then, 8 mL of deionized water was dropped into this aqueous solution while stirring, and the solution was stirred for 30 minutes. Then, the precipitate was centrifuged and collected, and heated at 80°C under an air atmosphere to obtain a powder (Example 2). Furthermore, as another synthesis method, first, 10 mL of TTIP and 50 mL of EtOH were mixed. Then, 3 mL of deionized water was dropped into this aqueous solution while stirring, and the solution was stirred for 30 minutes. Then, the precipitate was centrifuged and collected, and heated at 80°C under an air atmosphere to obtain a powder (Example 3).

[0043] FIG. 2A shows the X-ray diffraction patterns using CuKα radiation for the powders of Examples 1, 2, and 3. For reference, FIG. 2B shows the X-ray diffraction patterns using CuKα radiation for a powder of crystalline rutile-type titanium oxide (IV) (R-TiO2). As is clear from a comparison of FIG. 2A and FIG. 2B, no peaks were detected in the diffraction angle range associated with crystalline titanium oxide in Example 1 (TET+EtOH), Example 2 (TTIP+THF), and Example 3 (TTIP+EtOH). From this, it can be seen that the powders of Examples 1, 2, and 3 all contain TiO x Amorphous TiO having the composition (x is a positive number) x It was confirmed that the compound

[0044] 2. Constant current charge / discharge test The test electrode was a composite electrode containing the active material applied in each example, the counter electrode was an activated carbon electrode, and the reference electrode was an Ag / AgCl electrode (internal solution: saturated NaCl) (Example 4), an Ag / AgCl electrode (internal solution: saturated KCl) (Reference Example 1, Comparative Example 1), or an Ag / Ag +A three-electrode electrochemical cell was constructed using the electrode (internal solution: 100 mM AgOTf / EMI-TFSA) (Reference Example 2) and the electrolyte as the electrolyte composition applied in each example, and a constant current charge / discharge test was performed.

[0045] The active material and electrolyte composition of the test electrodes for each example were as follows: Example 4 Test electrode active material: amorphous TiO x Compound;TTIP+EtOH Electrolyte composition: protic ionic liquid; (HTFSA) 0.4 (DBU) 0.6 Reference example 1 Test electrode active material: amorphous TiO x Compound;TTIP+EtOH Electrolyte composition: Reference example 1-1 Acidic aqueous solution; 2.5M Li2SO4 :Reference example 1-2 Acidic aqueous solution; 2.5M Na2SO4 :Reference example 1-3 Acidic aqueous solution; 2.5M MgSO4 In Reference Examples 1 (1-1, 1-2, and 1-3), the respective metal salts are dissolved in water to generate Brønsted acids (protons and / or hydronium ions) in the electrolyte. + , Na + , Mg 2+ However, in the studies conducted by the present inventors, the intercalated ion is believed to be a proton. Reference example 2 Test electrode active material: crystalline rutile-type TiO2 (R-TiO2) Electrolyte composition: Reference Example 2-1 Aprotic ionic liquid; (HTFSA) 0.1 (EMI-TFSA) 0.9 Reference Example 2-2 Aprotic ionic liquid (HTFSA) 0.1 (Pyr 1,3 -TFSA) 0.9 Comparative Example 1 Test electrode active material: crystalline rutile-type TiO2 (R-TiO2) Electrolyte composition: buffer; 1M citric acid / trisodium citrate

[0046] 2.1 Preparation of electrolyte Example 4 The reagents used are shown below. 1,1,1-trifluoro-N-[(trifluoromethyl)sulfonyl]methanesulfonamide (HTFSA) (Kanto Chemical Co., Ltd.) 1,8-Diazabicyclo[5.4.0]undec-7-ene (DBU) (Sigma-Aldrich) As an example of an ionic liquid, a protic ionic liquid consisting of a combination of HTFSA and DBU was synthesized. That is, HTFSA was used as a Brønsted acid and DBU as a Brønsted base, and (HTFSA) 0.4 (DBU) 0.6 The mixture was prepared with a molar fraction of

[0047] Reference example 1 The reagents used are shown below. Lithium sulfate monohydrate (Li2SO4·H2O) (FUJIFILM Wako Pure Chemical Industries, Ltd.) Sodium sulfate (Na2SO4) (FUJIFILM Wako Pure Chemical Industries, Ltd.) Magnesium sulfate (MgSO4) (FUJIFILM Wako Pure Chemical Industries, Ltd.) The metal salts of each reagent were dissolved in water to prepare solutions with concentrations of 2.5 M Li2SO4, 2.5 M Na2SO4, and 2.5 M MgSO4, respectively.

[0048] Reference example 2 The reagents used are shown below. 1,1,1-trifluoro-N-[(trifluoromethyl)sulfonyl]methanesulfonamide (HTFSA) (Kanto Chemical Co., Ltd.) 1-Ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)amide (EMI-TFSA) (Kanto Chemical) N-Methyl-N-propylpiperidinium bis(trifluoromethanesulfonyl)amide (Pyr 1,3 -TFSA) (Kanto Chemical Co., Ltd.) As examples of ionic liquids, EMI-TFSA and Pyr 1,3 The aprotic ionic liquids used were EMI-TFSA, Pyr-TFSA, and HTFSA as the acid salt of the electrolyte. 1,3 -TFSA was used as the electrolyte solvent, and the following was performed in a glove box: (HTFSA) 0.1 (EMI-TFSA) 0.9 , (HTFSA) 0.1 (Pyr 1,3 -TFSA) 0.9 The mixture was prepared with a molar fraction of

[0049] Comparative Example 1 The reagents used are shown below. Citric acid (C(OH)(CH2COOH)2COOH) (FUJIFILM Wako Pure Chemical Industries, Ltd.) Trisodium citrate (Na3(C3H5O(COO)3)) (FUJIFILM Wako Pure Chemical Industries, Ltd.) The reagents were dissolved in water to prepare a phosphate buffer solution consisting of 1 M citric acid and 1 M trisodium citrate (1 M citric acid / trisodium citrate).

[0050] 2.2 Preparation of electrodes [Test pole] (Synthesis of active materials) Example 4, Reference Example 1 The amorphous active material was confirmed to be amorphous titanium oxide. It was synthesized by the same method as in Example 3. x The compound (TTIP+EtOH) powder was used.

[0051] Reference Example 2, Comparative Example 1 The reagents used are shown below. Hydrogen peroxide (H2O2) (FUJIFILM Wako Pure Chemical Industries, Ltd.) Glycolic acid (C2H4O3) (FUJIFILM Wako Pure Chemical Industries, Ltd.) Ammonia water (NH3) (Kanto Chemical) The crystalline active material was synthesized by hydrothermal method using rutile-type TiO2 (R-TiO2). First, among the reagents used in Example 1, TET was selected as the precursor, and EtOH was selected as the solvent, and amorphous TiO2 was synthesized by the same method as in Example 1. x A powder of the compound (TET+EtOH) was synthesized. Then, 40 mL of hydrogen peroxide and 1.6 mL of 70% glycolic acid were dropped into this powder, and the pH was adjusted to within the range of 4-9 using an aqueous ammonia solution, and the mixture was stirred for about 10 hours. The aqueous solution was then transferred to a hydrothermal vessel and subjected to hydrothermal treatment at 180°C for 48 hours to obtain a single-phase R-TiO2 powder.

[0052] (Preparation of composite electrode) Example 4, Reference Examples 1 and 2, Comparative Example 1 The samples and reagents used are shown below. Active material: TTIP+EtOH powder, R-TiO2 powder (synthesized) Conductive agent: Acetylene black (Denki Kagaku Kogyosha) Binder: Polyvinylidene fluoride (PVDF) (Kishida Chemical Co., Ltd.) Electrode substrate (current collector): Titanium foil (TR270C-H, film thickness: 2 μm) (Takeuchi Metal Foil and Powder Co., Ltd.) TTIP+EtOH powder or R-TiO2 powder: 80wt.%, acetylene black: 10wt.%, PVDF: 10wt.% were mixed in a weight ratio. Then, this sample and seven zirconia grinding balls (Ito Seisakusho Co., Ltd.) of φ10mm and about 3g were sealed in a zirconia pressure-resistant container (Ito Seisakusho Co., Ltd.) in a weight ratio of 1:30, and set in a planetary ball mill (P-6 classic line, Fritsch Co., Ltd.) to synthesize a slurry. Next, the synthesized slurry was applied to titanium foil using a Baker-type applicator (SA-101, Tester Sangyo Co., Ltd.) under the condition of 5.0mil, and then vacuum dried. The film thickness of the prepared electrode was 10μm, and the active material weight was 0.9-1.1mg cm -2 It was calculated that:

[0053] [Opposite] The reagents used are shown below. Active material: Activated carbon powder (Fujifilm Wako Pure Chemical Industries, Ltd.) Conductive additive: Denka Black (Denka) Binder: Carboxymethylcellulose sodium salt (CMC-Na) (average molecular weight (Mw) ~ 90,000, Sigma-Aldrich) Thickener: Styrene-butadiene rubber (SBR) (BM-400B (aqueous dispersion containing 40 wt.% modified styrene-butadiene copolymer), Zeon Corporation) Electrode substrate (current collector): Titanium foil (TR270C-H, film thickness: 2 μm) (Takeuchi Metal Foil and Powder Co., Ltd.) The weight ratio of activated carbon powder: 85 wt.%, denka black: 5 wt.%, CMC: 6 wt.%, and SBR: 4 wt.% was weighed out to a total of 2 g. The activated carbon powder, denka black, and CMC-Na were lightly mixed in a zirconia pressure-resistant container (Ito Seisakusho Co., Ltd.) together with seven zirconia grinding balls (Ito Seisakusho Co., Ltd.) of φ10 mm and approximately 3 g each, and further SRB and 6.5 mL of ion-exchanged water were added and sealed. This was set in a planetary ball mill (P-6 classic line, Fritsch Co., Ltd.) to synthesize a slurry. The synthesized slurry was then applied to titanium foil using a Baker-type applicator (SA-101, Tester Sangyo Co., Ltd.) at 10.0 mil, and then vacuum-dried.

[0054] [Reference pole] Example 4 Ag / AgCl electrode (internal solution: saturated NaCl): The reagents used are as follows: Ag / AgCl double junction reference electrode (EC Frontier) Sodium chloride (NaCl) (FUJIFILM Wako Pure Chemical Industries, Ltd.) A Ag / AgCl double junction reference electrode was immersed in the saturated NaCl system.

[0055] Reference Example 1, Comparative Example 1 Ag / AgCl electrode (internal solution: saturated KCl): The reagents used are as follows: Ag / AgCl double junction reference electrode (EC Frontier) Potassium chloride (KCl) (FUJIFILM Wako Pure Chemical Industries, Ltd.) An Ag / AgCl double junction reference electrode was immersed in the saturated KCl system. In addition, in order to prevent the formation of precipitates in the electrolyte, different internal solutions were used for Example 4 and the above example. However, this has almost no effect on the comparison of the measured values ​​with Example 4.

[0056] Reference example 2 Ag / Ag + Electrode (internal solution: 100 mM AgOTf / EMI-TFSA): The reagents used are as follows: Silver trifluoromethanesulfonate (AgOTf) (Kanto Chemical) 1-Ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)amide (EMI-TFSA) (Kanto Chemical) The Ag wire was immersed in a system in which 100 mM AgOTf was dissolved in EMI-TFSA.

[0057] 2.3 Constant current charge / discharge test The equipment used is shown below. Constant current test equipment (HJ-1001SD8, Hokuto Denko) Low temperature incubator (IQ822) (Yamato Scientific Co., Ltd.) The measurement conditions are as follows. Temperature: 25℃ (298K) Current density: Example 4; 335 mA g -1 (2C) :Reference example 1;335mA g -1 (2C) :Reference example 2;33.5mA g -1 (0.2C) : Comparative example 1; 335mA g -1 (2C) Potential range: Example 4; -1.7 to +0.2 V vs. Ag / AgCl in sat. NaCl :Reference example 1-1, 1-2;-1.5~+0.5V vs.Ag / AgCl in sat.KCl :Reference example 1-3;-1.4~+0.5V vs.Ag / AgCl in sat.KCl :Reference example 2-1, 2-2;-1.2~+0.25V vs.Ag / Ag + in 100mM AgOTf / EMI-TFSA :Comparative example 1;-1.1~+0.5V vs.Ag / AgCl in sat.KCl

[0058] The results are shown in Fig. 3A and Fig. 3B to Fig. 6. Fig. 3A is a graph showing the results of a constant current charge / discharge test according to Example 4. Fig. 3B is a graph showing cycle characteristics (changes in discharge capacity and coulombic efficiency) based on the constant current charge / discharge test according to Example 4. Fig. 4 is a graph showing the results of a constant current charge / discharge test according to Reference Example 1. Fig. 5 is a graph showing the results of a constant current charge / discharge test according to Reference Example 2. Fig. 6 is a graph showing the results of a constant current charge / discharge test according to Comparative Example 1.

[0059] In Reference Example 2 and Comparative Example 1, in which crystalline TiO2 was used as the test electrode active material, the reversible capacity associated with proton desorption was increased in Reference Example 2, in which an ionic liquid was used in the electrolyte composition, compared with Comparative Example 1, in which a buffer solution was used in the aqueous electrolyte. The discharge capacity of the first cycle in Comparative Example 1 was 100 mA hg -1 In contrast, in Reference Example 2-1 (EMI-TFSA), it was 179mA hg -1 , Reference example 2-2 (Pyr 1,3 -TFSA) is 186mA hg -1 And it was relatively good.

[0060] In Reference Example 1, in which an aqueous electrolyte was used as in Comparative Example 1, amorphous TiO x The discharge capacity of the first cycle of Reference Example 1 using the compound as the test electrode active material was 141 mA hg for Reference Example 1-1 (2.5M Li2SO4). -1 , Reference Example 1-2 (2.5M Na2SO4) is 154mA hg -1 , Reference Example 1-3 (2.5M MgSO4) is 147mA hg -1 And it was relatively good.

[0061] In addition, amorphous TiO xIn Example 4, in which the compound was used as the test electrode active material and an ionic liquid (a combination of HTFSA and DBU) was used as the electrolyte composition, the decrease in discharge capacity relative to the charge capacity was suppressed and the coulombic efficiency was greatly improved, compared to Reference Examples 1 and 2 in which either one was used. The coulombic efficiency in the first cycle of Reference Example 1 was 73% in Reference Example 1-1, 60% in Reference Example 1-2, and 70% in Reference Example 1-3. The coulombic efficiency in the first cycle of Reference Example 2 was 54% in Reference Example 2-1, and 70% in Reference Example 2-2. In contrast, in Example 4, the coulombic efficiency was greatly improved to 90% in the first cycle.

[0062] In addition, the discharge capacity of the first cycle of Example 4 was 120 mA hg -1 In the case of ionic liquid, since there are no H2O molecules in the electrolyte, a certain amount of discharge capacity was obtained, even under conditions where high-speed proton conduction such as the Grothas mechanism cannot be expected. Furthermore, as shown in FIG. 3B, the transition related to the charge-discharge cycle in Example 4 showed that the discharge capacity slightly declined at the beginning, but then stabilized, and stable proton desorption, i.e., discharge, was possible for at least up to 50 cycles. Since the protic ionic liquid has a slightly large viscosity, it is difficult for the proton conduction in the liquid to follow during charging and discharging, and the proton transport to the active material during charging becomes the rate-limiting factor, resulting in a slight decrease in discharge capacity. However, in combination with the amorphous active material, irreversible hydrogen generation is greatly suppressed, so that the Coulomb efficiency can be maintained at a high value even when cycles are repeated, and it is considered that overall stable discharge is possible. Thus, a protic ionic liquid consisting of a combination of HTFSA and DBU is used as an electrolyte, and amorphous TiO x Example 4, in which the compound was used as the test electrode active material, exhibited a greatly improved Coulombic efficiency compared to Comparative Example 1 and Reference Examples 1 and 2, and thus exhibited stable and excellent cycle characteristics. [Explanation of symbols]

[0063] 1 secondary battery, 2 positive electrode, 2A positive electrode substrate, 2B positive electrode active material, 3 separator, 4 negative electrode, 4A negative electrode substrate, 4B negative electrode active material, 5 electrolyte, 6 positive electrode exterior material, 7 negative electrode exterior material

Claims

1. A secondary battery in which reversible charging and discharging is performed by the transfer of protons or polyatomic ions composed of hydrogen atoms and nonmetallic atoms between a positive electrode and a negative electrode, The negative electrode active material contains an amorphous titanium oxide, The electrolyte composition contains an ionic liquid. A secondary battery characterized by:

2. The titanium oxide is TiO x (x is a positive number) x Being a compound 2. The secondary battery according to claim 1,

3. The TiO x The compound is a hydrolysis product of a crystalline titanium oxide salt.

3. The secondary battery according to claim 2,

4. The titanium oxide salt is tetraisopropyl orthotitanate, The TiO x The compound is a hydrolysis product of tetraisopropyl orthotitanate with ethyl alcohol.

4. The secondary battery according to claim 3,

5. The ionic liquid is a protic ionic liquid. The secondary battery according to any one of claims 1 to 4,